Rubinstein-Taybi Syndrome in a Male Child: Unusual Manifestations of a Rare Disease - Deepak Balikai; Varsha M Shetty; Raghavendra Rao; B Sathish Pai (Wolters Kluwer Medknow Publications, 2019)
Rubinstein-Taybi syndrome (RSTS) is a rare genetic disorder, characterized by intellectual disability, growth retardation, characteristic facial features, skeletal deformities, and other systemic involvement. Cutaneous involvement includes hirsutism, capillary hemangiomas, pilomatricomas, keloids, and hair abnormalities. Diagnosis of this condition is at times difficult due to overlapping clinical features and requirement of genetic mutation analysis which is not feasible in majority of the cases. Hence, it is imperative to know the typical dermatological features of RSTS which will help in clinical diagnosis in most of the cases.